2018
DOI: 10.1002/cre2.109
|View full text |Cite
|
Sign up to set email alerts
|

Development of an assessment strategy in preclinical fixed prosthodontics course using virtual assessment software—Part 1

Abstract: The purpose of this study was to develop an assessment strategy for preclinical foxed prosthodontics using a virtual assessment software. This descriptive study examined 80 collected ivory teeth from previous classes prepared during preclinical fixed prosthodontics course. Ivory teeth prepared for the complete cast (tooth no. 46), metal ceramic (teeth nos 24 and 46), and all ceramic (tooth no. 21) crowns were scanned and superimposed with their respective standard preparations. Differences between these teeth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Our study evaluated the effect of recently developed rubrics on the acquisition of psychomotor skills required for fixed prosthodontics. The method of assessment for Class B was partially objective as it used calculated data from Compare software such as %Comparison, averages of finish line width, and axial wall height 17, 18 . In our study, the use of virtual assessment software and contemporary rubrics for Class B resulted in students' ability in tooth preparation similar to that of Class A.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Our study evaluated the effect of recently developed rubrics on the acquisition of psychomotor skills required for fixed prosthodontics. The method of assessment for Class B was partially objective as it used calculated data from Compare software such as %Comparison, averages of finish line width, and axial wall height 17, 18 . In our study, the use of virtual assessment software and contemporary rubrics for Class B resulted in students' ability in tooth preparation similar to that of Class A.…”
Section: Discussionmentioning
confidence: 77%
“…However, a follow‐up study found that virtual assessment software grading did not correlate with the principles required for effective crown preparation 15 . In a further attempt to provide an objective assessment using virtual assessment software, contemporary rubrics were developed and implemented with Class B in our study 17, 18 . The results show that students trained following contemporary rubrics performed similarly to ones trained following conventional rubrics in a shorter period of the time.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations